Investigating the metabolic effects of conjugated linoleic acid isomers as monotherapy or combined with rosiglitazone: in vitro and in vivo studies - Chai, Boon Kheng (2020)
Conjugated linoleic acids (CLA) are dietary fatty acids commonly found in dairy and ruminant meats. CLA is found to be beneficial in treating the metabolic syndrome (MetS) and its major complication, type 2 diabetes mellitus. CLA is thought to exert its beneficial effect through activation of peroxisome proliferator activated receptors (PPAR) activity. Thus, CLA may be beneficial alone or in combination with current medications where it reduces side effect of conventional insulin sensitisers, such as rosiglitazone. The study was carried out via in vitro and in vivo approaches. For the in vitro study, the effects of CLA isomers and its combination with rosiglitazone on glucose production of HepG2 and H4IIE and gluconeogenic gene expression of HepG2 cells were examined. It was found that c9,t11-CLA isomer reduced glucose production in HepG2 and H4IIE cells compared to untreated control (p < 0.005), while, t10,c12-CLA had the opposite effect of increasing glucose production. c9,t11-CLA did not affect the ability of rosiglitazone in directly reducing glucose production. Reduction of glucose production by fenofibrate was not affected by either CLA isomer. c9, t11-CLA was found to decrease PEPCK expression in HepG2 cells (p < 0.05). The in vivo segment of the study was performed with ApoE null mice (n=29) fed Western diet for 20 weeks, divided into 5 groups, to examine the effect of 3 mg/day 1:1 mixture of c9,t11 and t10,c12 isomers of CLA on lipoprotein metabolism and insulin, leptin and adiponectin. The administration of 1:1 CLA isomeric mixture did not alleviate dyslipidemia caused by Western diet; instead simultaneous administration of CLA and rosiglitazone exacerbated dyslipidemia in ApoE null mice, particularly total plasma cholesterol (p < 0.001) and plasma LDL (p < 0.0001) compared with normal mice fed normal diet. While glucose, insulin and adiponectin level remain unchanged across groups, early administration of CLA irrespective of rosiglitazone led to reduction of leptin compared with mice fed only Western diet. It can be concluded that while c9,t11-CLA may exert benefits in MetS on the liver in vitro, the administration of CLA isomeric mixture with rosiglitazone exacerbates dyslipidemia in vivo that may be caused by t10,c12 isomer and thus, unable to ameliorate side effects of rosiglitazone.